Protestantiška Vokietijos knyga Lietuvos Didžiosios Kunigaikštystės protestantų bibliotekose XVI-XVIIa. - Lukšaitė, Ingė (Knygotyra, 1996)
Files and lists of the following 16th-17th c. libraries are analyzed: the library of King Žygimantas Augustas (part of the library reconstructed by A. Kawecka-Gryczowa - 960 titles), nobleman Salomon Rysiński (birth date unknown - 1625) in Vilnius (about 1000 titles), collections in 1674 given as a present to Slutsk boarding-school (74 books), Kėdainiai estate library of the mid-17th c. (183 titles), and the Vilnius Lutheran church library of the 16th-17th c. (185 titles). Identification of books indicated on the list of the Kėdainiai estate library made it possible to determine that this library belonged to Jonušas Radvila (1612-1655), who was the chief commander of the Army of GDL and Vilnius governor.All libraries were Latin with the exception of the Vilnius Lutheran church library, in which there were 8 books more in German than in Latin. A conclusion is made that the general trend in Lithuania to choose Latin as the language of intellectual information exerted influence also on the Vilnius Lutheran German community, in whose library there were only 8 books in German more than in Latin. Whereas, in Germany itself (according to the data obtained from the files of the book market in Frankfurt am Main), the number of theological books in German exceeded those in Latin by twice.As regards the living languages, there were sets of books in German, Polish, Lithuanian, Danish, French, and English. German and Polish books were most abundant. However, it should be pointed out that in Jonušas Radvila's library there were only 10 books in German and 3 books in Polish.Sets of books from Protestant Germany were only a constituent part of the libraries, taken together with abundant printed products from Switzerland and the Netherlands. Lithuanian Protestants preferred the books used by German university professors, especially the works of antique authors issued in the 16th-17th c., books on the history of European countries, texts of the Bible, and their explanations and interpretations. Among German Protestant authors, Philip Melanchthon was the most popular, next to Professor Justus Lipsius from the Netherlands. Readers were also interested in the works grounding educational reforms.